2019
DOI: 10.1029/2019gc008613
|View full text |Cite
|
Sign up to set email alerts
|

Interplay of Subduction Tectonics, Sedimentation, and Carbon Cycling

Abstract: Distinct differences were observed in geochemical signatures in sediments from two sites drilled in the upper plate of the Costa Rica margin during Integrated Ocean Drilling Program (IODP) Expedition 334. The upper 80 m at Site U1379, located on the outer shelf, shows pore water non‐steady state conditions characteristic of a declining methane flux. These contrast with analyses of the upper sediment layers at the middle slope site (U1378) that reflect steady state conditions. Distinct carbonate‐rich horizons u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
8
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
1
1

Relationship

3
4

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 82 publications
2
8
0
Order By: Relevance
“…The similarities in the profiles are most likely due to the similar responses that V, Mo, and U have to changing redox conditions in the sediments, particularly as related to their cycling with Fe and Mn minerals in these fine-grained deposits. Such behavior has been documented previously at this site (Torres et al, 2014;Riedinger et al, 2019).…”
Section: Site U1378supporting
confidence: 83%
See 2 more Smart Citations
“…The similarities in the profiles are most likely due to the similar responses that V, Mo, and U have to changing redox conditions in the sediments, particularly as related to their cycling with Fe and Mn minerals in these fine-grained deposits. Such behavior has been documented previously at this site (Torres et al, 2014;Riedinger et al, 2019).…”
Section: Site U1378supporting
confidence: 83%
“…In contrast to Site U1378, Site U1379 is characterized by distinct layers of authigenic carbonates as thick as 11 m in Unit II (see the Site U1379 chapter [Vannucchi et al, 2012c]; Riedinger et al, 2019). The formation of these layers is related to the tectonic history in this region.…”
Section: Study Sitesmentioning
confidence: 99%
See 1 more Smart Citation
“…Ocean drilling indicates ~1 km of uplift of the forearc continental shelf within only ~0.3 My, starting at ∼2±0.2 Ma, which was followed by equally fast subsidence of ∼1.5 km (refs. 4,83,85 ). The rapid vertical motion of the forearc, and retreat of the trench, suggests that the onset of Cocos Ridge subduction caused accelerating compression, followed by outer forearc removal and thinning by basal erosion 4,86 .…”
Section: And Supplementarymentioning
confidence: 99%
“…Those studies greatly advanced understanding of deep fluid sources at subduction zone plate interfaces (e.g. Hensen et al, 2004;Mau et al, 2007;Ranero et al, 2008;Kluesner et al, 2013;Riedinger et al, 2019), and identified a number of seep sites at which deep-sourced fluids might be sampled (e.g. Füri et al, 2010).…”
Section: Introductionmentioning
confidence: 99%